Body temperature programmable elastic shape memory form - Eng, Rayner Han Rong (Nanyang Technological University, 2024)
Shape memory technology refers to the use of materials which possesses shape memory properties or characteristic. This project research is a study on the shape memory effect of body temperature programmable elastic shape memory polymer.